THE UNIQUE PLACE AND IMPORTANCE OF THE SECURITIES MARKET (International journal of artificial intelligence, 2024)
this article describes the role of the securities market in the economy, its specific features, forms of legal regulation of the securities market in the Republic of Uzbekistan and normative legal documents, participants of the securities market, classification of types, information about the securities market.